Women and the colonial state : essays on gender and modernity in the Netherlands Indies 1900-1942 (2000)
In 19I5 a Dutch family in Surabaya had its pictures taken in the studio ofone of the famous photographers ofthe day.They took their Indonesian babu(nursemaid) along to be portrayed with their two children, in itself a highly unusual act. Pictures of a babu with children might occasionally be taken at home but very seldom in an official studio. Who they were we do not know. Only the name ofthe photographer remains, the Jewish Armenian Annes Kurkdjian. The three in the photograph are anonymous, except for their first names noted in the photo-album, 'Jantje and Agnes in the care ofBaboe Mina'. The album in which this picture was glued, got lost during the Japanese occupation of the former Netherlands Indies (or Dutch East-Indies) during the Second World War. It was one ofthe many that were rescued and collected by private initiative after 1945 and donated to the Royal Tropical Institute in Amsterdam in the late 1970S. Here I discovered the photo more than twenty years later at an exposition, when I was looking for illustrations for this book. Wardy Poelstra of Amsterdam University Press selected it from among many others for the cover. The picture is not meant to be a romantic signal ofthe happy, albeit rather earnest, relations within a colonial family. It offers a representation of both the literal and symbolic workload ofIndonesian women and serves as an emblem for the unequal gender and race relationships in the European household, in women's labour situations in rural Java, in the struggle for women's suffrage, and in the monogamy debate of1937, which are the subject ofthe following essays. The research for this volume was made possible by a grant from the Research Institute of History and Culture (Onderzoeksinstituut voor Geschiedenis en Cultuur) at Utrecht University, for which I am highly grateful. Not least because it also brought me, a colonial historian at Utrecht University, a part-time position at the Women Studies Department at the same university for the years 1992-1997.The creative academic community ofthe department chaired by Rosi Braidotti offered me an inspiring environment in which to continue my research on the construction ofgender in colonial Indonesia. The interdisciplinary discussions with my colleagues in the monthly 'Intellectual Atelier' served as a sparkling context for this book. My sincerest thanks go to those with whom I worked most closely: Rosi Braidotti, Rosemarie Buikema, Esther Captain, Denise De Costa, Geertje Mak, Maaike Meijer, Boukje Prins, Berteke Waaldijk and Gloria Wekker.